Preventive factors for urinary incontinence - Hirayama, Fumi; Lee, Andy (Nova Science Publishers, 2013)
Urinary incontinence (UI) is a distressing condition for middle aged and older adults. The prevalence of UI varies substantially worldwide, depending on the definition adopted, the population being studied, and the instrument used for assessing leakage. Established risk factors are the female gender, obesity, advanced age and cigarette smoking. The main treatments include pharmacological prescriptions, conservative therapies (such as pelvic floor muscle exercise, biofeedback, electrical stimulation), and surgery. This chapter reviews the epidemiological evidence on emerging factors which may protect against the disease. Increasing green tea consumption appears to reduce the prevalence of UI among women. Low alcohol intake particularly beer is inversely associated with male UI, whereas the corresponding relationship for women remains inconsistent. Moreover, physical activity in daily life may mediate against the development of UI. Further research is required to understand the biological mechanisms concerning these factors, especially by gender and incontinence subtype, in order to prevent this bothersome condition for the aging population.